Review on the Safety and Sustainability of Autonomous Vehicles: Challenges and Future Directions - Uzzaman, Asif; Adam, Md Ibrahim; Alam, Shahin; Basak, Pallab (Peneliti Teknologi Teknik Indonesia, 2025)
Autonomous vehicles (AVs) represent a major advancement in transportation technology, offering significant benefits such as enhanced road safety, reduced traffic congestion, and improved mobility. However, the widespread deployment of AVs faces key obstacles, including sensor limitations under adverse weather conditions, ethical decision-making in complex scenarios, regulatory challenges, and data privacy concerns. This paper examines these challenges and proposes potential solutions. Key challenges include improving sensor fusion and AI algorithms to enhance perception and decision-making, developing standardized ethical guidelines for autonomous systems, and establishing consistent legal and regulatory standards across regions. Additionally, ensuring cybersecurity and addressing data privacy issues are critical for maintaining the safety and trust of AV users. The future of AVs also depends on advancements in infrastructure, such as the development of smart roads and Vehicle-to-Everything (V2X) communication systems, as well as reducing production costs to increase accessibility. Furthermore, raising public awareness and fostering acceptance through education and transparent communication about AV benefits is vital. The paper concludes that with ongoing research, innovation, and collaboration, AVs have the potential to revolutionize transportation, offering a safer, more efficient, and sustainable future for mobility.